Learning Arabic using the Al-Arabiyah Baina Yadaik Book at the University - Siti Arafa; Imam Fauji (Indonesian Journal of Islamic Studies, 2022)
The purpose of this study was to describe Arabic language learning using the book Al-Arabiyah Baina Yadaik Di Mustawa Tamhidi Di Ma'had Umar Bin Al-Khattab Putri Muhammadiyah University of Sidoarjo. This study uses a qualitative research approach. Data collection techniques in this study by carrying out observations, interviews and documentation. The data analysis technique used in this research is Miles and Huberman data analysis technique. The results showed that: Preparation before learning Arabic, namely: Preparing the Lesson Plan (RPP), opening a dictionary, preparing learning media and studying the pattern of practice questions. The process of learning Arabic, which uses a communicative method. Evaluation of Arabic learning, namely formative evaluation and summative evaluation. Supporting factors are learning media, dictionaries, preparation, motivation and google. While the inhibiting factor is that at the beginning of learning there are some students who do not have the al-arabiyah baina yadaik book, when students do not do the assignments given by the teacher, students do not bring dictionaries into the classroom while learning, and the learning audio has not been updated.